Expenditure decisions on international remittances received by households in Ghana - Eugene Danquah Ofori-Appiah; Kwaku Dwumor Kessey; Eric Oduro-Ofori (Cogent Social Sciences, 2024)
People migrate to take advantage of the opportunities in developed countries. They also seek to improve the lives of the families they have left behind. This thought is actualized through the international remittances the migrants send back home. When individuals receive international remittances, they make expenditure decisions, which are influenced by several factors including restrictions attached to the remittance. By incorporating the free balance concept into remittance studies, the study sought to analyze the effects of restricted and unrestricted nature of international remittances on expenditure decisions in Kumasi. Most remittance studies in Ghana have not included the restrictions on international remittances in their research; hence, including them in the study broadens the understanding of remittance utilization in Ghana. The study relied on pragmatism as the philosophical underpinning and selected an inductive approach as the research approach. The research design was the explanatory design. The study employs the random sampling method to select the remittance recipients as the study’s respondents. The study gathered primary and secondary data. The primary data collection was made through a field-based questionnaire administration. A semi-structured questionnaire was selected to help the researcher narrow down some areas or topics to address. The source of secondary data was obtained largely from financial institutions, research journals, and books. With a calculated sample size of 712, at a 0.05 margin of error from total respondents of 2760, the study had a response rate of 96.77%. The findings revealed that the majority of remittances (58.02%) received came with no instructions. Most of the instructions on the restricted remittances were related to family support. The use of international remittances influences the subjective well-being of recipients of international remittances. The study has shed light on the effects of the restricted and unrestricted nature of international remittances on expenditure decisions in Kumasi. The findings indicate that unrestricted remittances have a more significant impact on the subjective well-being of the recipients. The study has also highlighted the need for policymakers and remittance service providers to develop policies and products that cater to the needs of the recipients.